2016
DOI: 10.1159/000448916
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Obesity to Performance in Verbal Abilities, Processing Speed, and Cognitive Flexibility in Old Age: The Role of Cognitive Reserve

Abstract: Aims: The present study set out to investigate the relation of obesity to performance in verbal abilities, processing speed, and cognitive flexibility and its interplay with key correlates of cognitive reserve in a large sample of older adults. Methods: A total of 2,812 older adults served as a sample for the present study. Psychometric tests on verbal abilities, processing speed, and cognitive flexibility were administered. In addition, individuals were interviewed on their weight and height (to calculate bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 35 publications
11
29
0
2
Order By: Relevance
“…Specifically, the relations of psychological stress to cognitive performance were reduced in individuals with higher education, a higher cognitive level of the first profession practiced after education, a larger number of midlife leisure activities, a larger number of significant family members, and a larger number of close friends. This is in line with studies showing that cognitive reserve and social capital may offset the detrimental influences of physiological stress on cognitive functioning in old age [2, 12, 21, 36] and extends prior evidence suggesting that the relation of psychological stress to cognitive functioning is smaller in individuals with higher scores in a late-life proxy of cognitive reserve [37], with data based on a comprehensive set of key life course markers of cognitive reserve and social capital in a large sample of older adults in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, the relations of psychological stress to cognitive performance were reduced in individuals with higher education, a higher cognitive level of the first profession practiced after education, a larger number of midlife leisure activities, a larger number of significant family members, and a larger number of close friends. This is in line with studies showing that cognitive reserve and social capital may offset the detrimental influences of physiological stress on cognitive functioning in old age [2, 12, 21, 36] and extends prior evidence suggesting that the relation of psychological stress to cognitive functioning is smaller in individuals with higher scores in a late-life proxy of cognitive reserve [37], with data based on a comprehensive set of key life course markers of cognitive reserve and social capital in a large sample of older adults in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, in line with that, recent empirical evidence suggests that cognitive reserve (in terms of e.g. higher education, higher cognitive level of job, and greater engaging in leisure activities) may offset the detrimental influences of strong physiological stressors such as metabolic syndromes and chronic diseases (e.g., unfavorable blood fat level, obesity, and hypertension) on cognitive performance (e.g., memory and executive functioning) in old age [2, 12, 36]. Likewise, with respect to compensation of physiological stressors by social capital, Bennett et al [21] found in a sample of 89 older adults that social network size moderated the negative association between Alzheimer disease pathology and cognitive performance (semantic memory and working memory).…”
Section: Introductionmentioning
confidence: 70%
“…In individuals with healthy cognitive functioning, these mechanisms contribute to the adaptation of brain activity when the task difficulty level is increased and thereby enhance cognitive performance [4]. Empirically corroborating the predictions of the cognitive reserve concept, both correlational and causal evidence showed that longer education in early life, cognitively demanding occupation in midlife, and cognitive leisure activity in midlife and old age contribute to the buildup of cognitive reserve during the life course and are related to better cognitive functioning such as memory and executive functioning in old age [5,6,7,8,9,10,11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 96%
“…Notably, recent evidence suggests that cognitive reserve (in terms of higher education and greater engagement in cognitive leisure activity) may offset the detrimental influences of metabolic syndromes such as obesity on cognitive performance (e.g., executive functioning) in old age [12]. In terms of such compensation effects, the cognitive reserve concept postulates structural and functional mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation